2017
DOI: 10.1001/jamadermatol.2017.3109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Industry Payments Among Dermatology Clinical Practice Guidelines Authors

Abstract: IMPORTANCEIt is well documented that financial conflicts of interest influence medical research and clinical practice. Prior to the Open Payments provisions of the Affordable Care Act, financial ties became apparent only through self-disclosure. The nature of financial interests has not been studied among physicians who develop dermatology clinical practice guidelines.OBJECTIVE To evaluate payments received by physicians who author dermatology clinical practice guidelines, compare disclosure statements for acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 12 publications
5
92
1
Order By: Relevance
“…The objective data from the OP program is a valuable tool for transparency because some authors of CPGs fail to disclose relevant ties to industry. An analysis of 40 authors from three CPGs published by the American Academy of Dermatology in 2013 to 2016 demonstrated that 55% of the disclosure statements were discrepant from OP data and that 15% (6 of 40) of authors reported no COIs yet received significant industry payments (38). Although our study was not designed to compare every payment from the OP database with self-disclosures, we did come across several noticeable discrepancies.…”
Section: Payments To Authors Of Cpgsmentioning
confidence: 80%
“…The objective data from the OP program is a valuable tool for transparency because some authors of CPGs fail to disclose relevant ties to industry. An analysis of 40 authors from three CPGs published by the American Academy of Dermatology in 2013 to 2016 demonstrated that 55% of the disclosure statements were discrepant from OP data and that 15% (6 of 40) of authors reported no COIs yet received significant industry payments (38). Although our study was not designed to compare every payment from the OP database with self-disclosures, we did come across several noticeable discrepancies.…”
Section: Payments To Authors Of Cpgsmentioning
confidence: 80%
“…74 Additionally, if AI does improve medical care, it will be important to pass those improvements on to those populations who cannot afford them. AI MLCs will likely be sold with and for implementation with certain medical technologies.…”
Section: Future Challengesmentioning
confidence: 99%
“…It will be important to anticipate conflicts of interest, which may be similar to precautions that exist when dealing with medical companies with a financial interest. 74 Additionally, if AI does improve medical care, it will be important to pass those improvements on to those populations who cannot afford them. The responsibility for advocating this will likely fall to healthcare professionals due to competing financial interests of medical companies.…”
Section: Future Challengesmentioning
confidence: 99%
“…Ensuring objectivity and neutrality is important in clinical practice guidelines development, but previous research shows that authors of clinical practice guidelines may become critical marketing promotion targets of pharmaceutical companies [3,9,10]. In reality, they had strong financial conflicts of interest; the authors of national comprehensive cancer centre guidelines received an average of $10 011 in a year [11]; 81.6% of the dermatology [10] and 53% of the gastroenterology clinical practice guideline authors had financial relationships with industrial companies [12]. Similar databases have been developed in Germany and the UK, which also reveal financial ties between the industry and physicians [9,13].…”
Section: Financial Ties Between Clinical Practice Guidelinesdauthors mentioning
confidence: 99%